1983
DOI: 10.1007/bf00388075
|View full text |Cite
|
Sign up to set email alerts
|

The spatial and temporal distribution pattern of the stoat (Mustela erminea L.)

Abstract: The distribution and movements of two stoat populations were studied by capture-recapture and tracking in the Swiss Jura Mountains. On the Brévine area in summer 1977 the population was at a high density phase and evenly distributed. A well established intrasexual territorial system was observed, with a high degree of sedentarity in adults. During the decline and the following phase of scarcity, the stoats were progressively restricted to a peat-bog area and the territorial system broke down. The adult males b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
9

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 11 publications
3
16
0
9
Order By: Relevance
“…The average home-range areas found in this study were far smaller than those reported from anywhere else in New Zealand (Table 5), and were closer in size to the home ranges of stoats recorded in the Northern Hemisphere (10-50 ha ;Erlinge 1977;Debrot & Mermod 1983). In New Zealand, small home ranges have been found in beech forest in years of high prey abundance following an irruption in mouse numbers (Murphy & Dowding 1995), and, additionally, in areas of high prey density around Murphy & Dowding 1995.…”
Section: Home-range Areasupporting
confidence: 45%
See 1 more Smart Citation
“…The average home-range areas found in this study were far smaller than those reported from anywhere else in New Zealand (Table 5), and were closer in size to the home ranges of stoats recorded in the Northern Hemisphere (10-50 ha ;Erlinge 1977;Debrot & Mermod 1983). In New Zealand, small home ranges have been found in beech forest in years of high prey abundance following an irruption in mouse numbers (Murphy & Dowding 1995), and, additionally, in areas of high prey density around Murphy & Dowding 1995.…”
Section: Home-range Areasupporting
confidence: 45%
“…Stoats are normally thought to maintain intrasexual territories, in which individuals of the same sex maintain territories excluding each other, but the territories of males and females overlap extensively (Erlinge 1977;Pounds 1981;Debrot & Mermod 1983). Powell (1979Powell ( , 1994 suggests that intrasexual territories of mustelids may break down in years with very high or very low prey densities.…”
Section: Introductionmentioning
confidence: 98%
“…The prevailing, relatively barren habitat types often cover vast areas, whereas patch sizes for more productive habitats usually only range from a few hundreds of square metres to a couple of hectares (Kalliola, 1939;Anon, 1980). Although small herbivorous animals often have home ranges of this size or even smaller, even the least carnivores cover substantially larger areas during their normal, daily movements (Erlinge, t974, 1977;King t975;Debrot and Mermod, 1983;Oksanen et al, 1991). Thus carnivores living in areas at the transition between the three-link and two-link ecosystems of Fretwell (1977) and Oksanen et al (1981) will often face a situation where their home ranges or territories consist of an archipelago of favourable patches, embedded in a matrix of barren ground.…”
Section: -7653mentioning
confidence: 99%
“…Regardless of the season during which reproduction occurs, male activity and movements generally increase when they are searching for mates (Gerell 1970;King 1975;Debrot and Mermod 1983;Sandell 1986;Arthur and Krohn 1991). Presumably the polygynous mating system that is thought to characterise most mustelids demands that males engage in extensive movements in search of females.…”
Section: Social and Reproductive Behaviourmentioning
confidence: 99%